The Revolution in Visual Creation: Generative Artificial Intelligence - Casas Arias, Miguel; Priego Díaz, Alejandro; Lara-Martínez, Maria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The integration of artificial intelligence (AI) in audiovisual creation is redefining the limits between human creativity and technological potential and its use is widespread on social networks. This research will review the technical background and aims to analyze the application of artificial intelligence in the different stages of visual production, where it will be studied whether the communication professional can take advantage of their knowledge to get greater performance from these tools. The conclusions determine that artificial intelligence is involved in the emergence of new forms of artistic and communicative expression.